Orbital Stability of the Sum of $N$ Peakons for the CH-mCH Equation (Journal of Nonlinear Modeling and Analysis, 2025)
This paper is concerned with a generalization of the modifiedCamassa-Holm equation with both cubic and quadratic nonlinearities (alsoknown as the CH-mCH equation). We mainly prove the orbital stability ofthe train of peakons for the CH-mCH equation in energy space, using energyarguments and combining the method of orbital stability of a single peakonwith the monotonicity of the local energy norm.
Keywords: Camassa-Holm equation; CH-mCH equation; peakons; multi-peakons; orbital stability.